Extra cultum nullus usus: il trattamento degli altari nel tempo della dismissione dei luoghi sacri, tra 'valore culturale' e 'interesse religioso' - Tomer, Alberto (Il diritto ecclesiastico, 2024)
Extra cultum nullus usus. The treatment of altars in the time of the decommissioning of sacred places, between ‘cultural value’ and ‘religious interest’ ∙ Within the already debated theme of the relegation of sacred places to profane use, scholars have paid a somewhat alarmed attention to the references found in the most recent documents by the dicasteries of the Roman Curia on altars, regarding which ‘the canonical practice of destroying the table’ is repeatedly recalled. In response to these statements, there has sometimes been an attempt to downsize the ‘shocking’ impact of requests which appear to be in stark contrast with the needs of safeguarding cultural heritage. It seems appropriate, however, to guard against the temptation to set aside these appeals too hastily, almost considering them the anachronistic fruit of unfounded concerns or despairing of their compatibility with the ius canonicum : in this perspective, the essay proposes some interpretative hypotheses in order to identify, from a systematic viewpoint, the correct placement of the aforementioned indications.